Components of the Indonesian Language and Literature Learning Curriculum - PURWANTI, Christina; PUTRAYASA, Ida Bagus; SUDIANA, I Nyoman; WISUDARIANI, Ni Made Rai (PT Keberlanjutan Strategis Indonesia, 2024)
Curriculum, derived from the Latin